Emerging Roles of Aldehyde Dehydrogenase Isoforms in Anti-cancer Therapy Resistance - Zanoni, Michele; Bravaccini, Sara; Fabbri, Francesco; Arienti, Chiara (Frontiers in Medicine, 2022)
Aldehyde dehydrogenases (ALDHs) are a family of detoxifying enzymes often upregulated in cancer cells and associated with therapeutic resistance. In humans, the ALDH family comprises 19 isoenzymes active in the majority of mammalian tissues. Each ALDH isoform has a specific differential expression pattern and most of them have individual functional roles in cancer. ALDHs are overexpressed in subpopulations of cancer cells with stem-like features, where they are involved in several processes including cellular proliferation, differentiation, detoxification and survival, participating in lipids and amino acid metabolism and retinoic acid synthesis. In particular, ALDH enzymes protect cancer cells by metabolizing toxic aldehydes in less reactive and more soluble carboxylic acids. High metabolic activity as well as conventional anticancer therapies contribute to aldehyde accumulation, leading to DNA double strand breaks (DSB) through the generation of reactive oxygen species (ROS) and lipid peroxidation. ALDH overexpression is crucial not only for the survival of cancer stem cells but can also affect immune cells of the tumour microenvironment (TME). The reduction of ROS amount and the increase in retinoic acid signaling impairs immunogenic cell death (ICD) inducing the activation and stability of immunosuppressive regulatory T cells (Tregs). Dissecting the role of ALDH specific isoforms in the TME can open new scenarios in the cancer treatment. In this review, we summarize the current knowledge about the role of ALDH isoforms in solid tumors, in particular in association with therapy-resistance.